Carbohydrate compositional trends throughout Holocene sediments of an alpine lake (Lake Cadagno) - Gajendra, Niroshan; Berg, Jasmine S.; Vogel, Hendrik; Deng, Longhui; Wolf, Sarah M.; Bernasconi, Stefano M.; Dubois, Nathalie; Schubert, Carsten J.; Lever, Mark A. (Frontiers in Earth Science, 2023)
Carbohydrates are a ubiquitous constituent of organisms and contribute significantly to sedimentary organic carbon pools. Yet, the factors that control the degradation and long-term preservation of sedimentary carbohydrates are not well understood. Here, we investigate carbohydrate pool sizes and chemical compositions in high-altitude, meromictic Lake Cadagno (Switzerland) over a 13,500-year-old sedimentary succession that has recorded past changes from oxic to anoxic conditions and consists mostly of intercalations of lacustrine sediments and terrestrial-derived sediments. Analyses of the organic matter chemical composition by pyrolysis gas chromatography /mass spectrometry (Py-GC/MS) show that carbohydrates are selectively preserved over other organic matter constituents over time. The carbohydrate pyrolysis products levosugars (potentially cellulose-derived) and (alkyl)furans and furanones (potentially pectinderived) dominate both lacustrine and terrestrially derived sediment layers, suggesting aquatic and terrestrial-derived sources of these compounds. Carbohydrate monomer analyses indicate galactose and glucose as dominant monomers and show no clear differences between aquatic and terrestrial organic matter. No clear impacts of past changes in redox conditions on carbohydrate compositions were observed. Our study shows that carbohydrates are a major contributor to sedimentary organic carbon burial in Lake Cadagno and indicates the effective preservation of both aquatic and terrestrial derived carbohydrates over millennia in lake sediments.